Prototyping a lightweight encryption on a field programmable gate array for securing tele-control data - Jidin R.; Tukijan S.N.; Al-Bahadly I.; Jamil N.; Qassim Q.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computation theory; Control systems; Data acquisition; Data privacy; Field programmable gate arrays (FPGA); Hardware security; Intelligent control; Internet of things; Light emitting diodes; Field programmable logic; Galois fields; Light-weight cryptography; Lightweight encryption; Securing SCADA; Cryptography